Temperature distribution in a composite prismatic rod in the case of heat generation in the circular, cylindrical concentric core. - Laura, P. A. A.; Sánchez Sarmiento, G. (Elsevier, 1979)
Fil: Laura, P. A. A. Comisión Nacional de Energía Atómica; Argentina